Transfection and expresion of the human fibroblast growth Factor-10 (hFGF-10) in mammalian cells - Nhi, Nguyen Bich; Suzuk, Masashi (Academia Journal of Biology, 2015)
We have constructed a pcDNA 3.1.(-)Myc-His Version B vector for expression of the hFGF-10 recombinant proteins in the COS-1 and COS-7 cells. LipoFectamin 2000 (LF-2000) and SuperFect (SF) were used for transient transfection. The expression of hFGF-10 recombinant proteins in COS-1 and COS-7 cells was analysed by SDS-PAGE following Western-Blotting analysis using anti-histidine antibody. The results showed that hFGF-10 proteins were secreted and expressed inseveral glycosylated and non-glycosylated forms in the cells and in the culture medium.